Statistics of Annual Earnings in OECD Countries - Grubb, David (OECD Labour Market and Social Policy Occasional Papers, 1990)
Existing multi-country earnings statistics generally relate to only a fraction of the economy's industries and occupations, often to manual workers in manufacturing industry. This paper discusses the annual basis of measurement, which has particular advantages when aggregations or comparisons of earnings need to be made across sectors, occupations, or countries that have markedly differing payment systems. Three main types of statistic of annual earnings are identified: estimates of annual earnings of the Average Production Worker (in manufacturing only), made in connection with OECD calculations of tax rates; aggregate wages and salaries per employee, corrected onto a full-time equivalent basis; and statistics based on individual data, which may come from household surveys, employer surveys or tax and social security records. Some comparisons among the available statistics examine to what extent the differing indicators give similar impressions as regards the level and trend of earnings